IMPROVING THE ABILITY TO USE ACCOUNTING SOFTWARE AS AN EFFORT TO IMPROVE THE QUALITY OF GRADUATES IN PREPARING FINANCIAL REPORTS AT SMAN 1 DEWANTARA AND SMKN 1 DEWANTARA ACEH UTARA - Nurhasanah; Murhaban; Nur Afni Yunita; Husaini; Muhammad Yusra (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2023)
This program is implemented at SMAN 1 Dewantara and SMKN 1 Dewantara. The problems faced by partners, namely students of SMAN 1 Dewantara and SMKN 1 Dewantara are; 1) Problems regarding the aspect of students' ability to make simple financial reports. 2) The problem of lack of knowledge and skills in using accounting software to produce effective and efficient financial reports. The aim of this activity is to find solutions to the problems faced by partners, namely students of SMAN 1 Dewantara and SMKN 1 Dewantara which the PKM Team carries out in community service programs, through mentoring and training. Preparing financial reports and using accounting software to improve the quality skills of SMAN 1 graduates Dewantara and SMKN 1 Dewantara.The method or approach offered and agreed upon with partners, namely SMAN 1 Dewantara and SMKN 1 Dewantara, is discussion of guidance, training, mentoring and evaluation of training results by holding skills tests.The outputs achieved by the PKM team are mandatory outputs in the form of; Service Reports, Publication of articles in OJS-based service journals or national seminar proceedings, Publication of activities in print or online media, and Collaboration documents with partners and additional output in the form of Copyright (IPR) service reports.